HUMANISM IN TAGORE: A STUDY OF LITERARY WORKS (International Journal of Food and Nutritional Sciences, 2022)
This research article explains the power of Humanism in literature , highlighting on its capacity to empower everyone in the society. This paper Challenges the existing in equalities. Humanist Literature empowers leaders to promote equality . Humanist concept in literature and its power to shape insight. Literature has played a major role in reshaping the society. Humanist Consciousness in literature brings social change , empower individuals to promote an equitable society. Tagore’s humanism is spiritualistic some of his stories , articles and lectures reflect his philosophy of Humanism, His lectures were complied in his book, ‘ The Religion Of Man ‘ In these lectures the poet has explained and stated “ Religion inexilably concentrates itself on humanity , which illumines our reason , inspires out wisdom , stimulates our love , claims our intelligent service. His spiritualistic humanism was developed with the different experience of life.